A Network Analysis Investigation of the Comorbidity Between Sleep Dysfunction and PTSD Symptomatology Among Filipino Domestic Workers in Macao (SAR) China - Wang, Siyuan (Archīum Ateneo, 2021)
Posttraumatic stress disorder (PTSD) is highly comorbid with sleep dysfunction. This association was previously explained based on cognitive and emotional dysfunction. The current study extends this literature by investigating the symptom level comorbidity of sleep dysfunction and DSM-5 PTSD utilizing a network approach. Participants were trauma-exposed female Filipino domestic workers (N = 1241). Network analysis was applied to 23 items: 18 items from PCL-5 measuring PTSD (Community 1) and 5 items from PSQI assessing sleep dysfunction (Community 2). The results showed that the symptoms within each community had the strongest correlations. Bridge connections were identified between the sleep dysfunction and PTSD symptom communities. Symptoms with the highest bridge strength were concentration difficulties, recklessness, irritability, and sleep disturbance. This is among the first studies investigating the comorbidity between PTSD and sleep dysfunction from the network approach. Future interventions may be developed that emphasize the bridge symptoms to address comorbidity among trauma exposed migrants.